Karyotype rearrangements and telomere analysis in Myzus persicae (Hemiptera, Aphididae) strains collected on Lavandula sp. plants - Mauro Mandrioli (Comparative Cytogenetics, 2014)
Karyotype analysis of nine strains of the peach-potato aphid Myzus persicae (Sulzer, 1776), collected on Lavandula sp. plants, evidenced showed that five of them had a standard 2n = 12 karyotype, one possessed a fragmentation of the X chromosome occurring at the telomere opposite to the NOR-bearing one and three strains had a chromosome number 2n = 11 due to a non-reciprocal translocation of an autosome A3 onto an A1 chromosome. Interestingly, the terminal portion of the autosome A1 involved in the translocation was the same in all the three strains, as evidenced by FISH with the histone cluster as a probe. The study of telomeres in the M. persicae strain with the X fission evidenced that telomerase synthesised de novo telomeres at the breakpoints resulting in the stabilization of the chromosomal fragments. Lastly, despite the presence of a conserved telomerase, aphid genome is devoid of genes coding for shelterin, a complex of proteins involved in telomere functioning frequently reported as conserved in eukaryotes. The absence of this complex, also confirmed in the genome of other arthropods, suggests that the shift in the sequence of the telomeric repeats has been accompanied by other changes in the telomere components in arthropods in respect to other metazoans.